2010
DOI: 10.1016/j.chom.2010.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Coronaviruses Hijack the LC3-I-Positive EDEMosomes, ER-Derived Vesicles Exporting Short-Lived ERAD Regulators, for Replication

Abstract: Coronaviruses (CoV), including SARS and mouse hepatitis virus (MHV), are enveloped RNA viruses that induce formation of double-membrane vesicles (DMVs) and target their replication and transcription complexes (RTCs) on the DMV-limiting membranes. The DMV biogenesis has been connected with the early secretory pathway. CoV-induced DMVs, however, lack conventional endoplasmic reticulum (ER) or Golgi protein markers, leaving their membrane origins in question. We show that MHV co-opts the host cell machinery for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
491
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(510 citation statements)
references
References 39 publications
14
491
1
4
Order By: Relevance
“…In support of this, electron microscopy showed that EDEM1 is primarily localized in double-membrane buds that form outside canonical ER exit sites, known as EDEMosomes (Zuber et al 2007;Le Fourn et al 2009;Reggiori et al 2010). At steady state, short-living ERAD components like EDEM1 and OS-9 appeared to be engulfed in these buds in a COPII-independent manner and degraded without the attachment of nonlipidated LC3.…”
Section: Other Degradation Pathwaysmentioning
confidence: 78%
“…In support of this, electron microscopy showed that EDEM1 is primarily localized in double-membrane buds that form outside canonical ER exit sites, known as EDEMosomes (Zuber et al 2007;Le Fourn et al 2009;Reggiori et al 2010). At steady state, short-living ERAD components like EDEM1 and OS-9 appeared to be engulfed in these buds in a COPII-independent manner and degraded without the attachment of nonlipidated LC3.…”
Section: Other Degradation Pathwaysmentioning
confidence: 78%
“…Our results suggest that EDEM1 and EDEM3 play a role in delivery of viral glycoproteins to the SEL1L-containing ubiquitin-ligase complex. It has recently been reported that coronavirus infection causes an accumulation of EDEM1 in membrane vesicles which are sites of viral replication, but that EDEM1 is not required for coronavirus replication (23). To our knowledge, the present study is the first to demonstrate regulation of the viral life cycle by ERAD machinery through interaction of EDEMs with viral glycoproteins.…”
Section: Discussionmentioning
confidence: 65%
“…Our results show that tetrandrine promoted the expressions of LC3-I and -II (Fig. 4) and it is well documented that LC3-I and -II are involved in the development of autophagy and both proteins play an important role during autophagy (56)(57)(58). Furthermore, other proteins such as Atg-5, Atg-7 and beclin-1 are also involved in the development, especial Atg-5 is essential for autophagy (59)(60)(61)(62).…”
Section: Discussionmentioning
confidence: 93%